Political Participation: Essence And Implications - Shoimov Alisher Rahmatulloevich (Peerian Journals Publishing, 2024)
This article analyzes political beliefs and experiences of participation in the political world, legitimizes the legal and political significance of Etgan Turlari and its special legal form, and analyzes political beliefs and political beliefs based on evidence, evidence, evidence, evidence, e, evidence, evidence, evidence, evidence, evidence
Keywords: Political participation; political institution; political faolik